2014
DOI: 10.1177/2325967114532424
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Tightness of the Hip Joint and Elbow Pain in Adolescent Baseball Players

Abstract: Background:Repetitive tensile stresses from valgus torque can induce elbow injury in adolescent baseball players. Insufficient hip range of motion (ROM) can change throwing mechanics, reducing the transfer of energy from the lower to the upper extremities. Thus, hip ROM limitations may force the upper extremities to bear the burden of a strong throw. Improper pitching mechanics caused by insufficient hip ROM are thought to increase valgus torque on the elbow when throwing, increasing the risk of elbow injury.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 29 publications
3
73
1
Order By: Relevance
“…Impaired hip ROM may be a relative factor needing to be considered for injury prevention and athletic performance, thus should be considered for inclusion when prescribing exercises for these individuals. 14,19,23 These data are the first to be reported among WT participants, thus should be considered for clinical practice when managing such patients. WT participants may have different values based upon the types of WT activities, performed, thus general population normative values may not be relevant.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Impaired hip ROM may be a relative factor needing to be considered for injury prevention and athletic performance, thus should be considered for inclusion when prescribing exercises for these individuals. 14,19,23 These data are the first to be reported among WT participants, thus should be considered for clinical practice when managing such patients. WT participants may have different values based upon the types of WT activities, performed, thus general population normative values may not be relevant.…”
Section: Discussionmentioning
confidence: 75%
“…The connection between hip ROM deficits and injury has been reported for other athletic activities. For baseball, a higher risk of shoulder, 13 elbow, 14 and groin injuries 15 have been found in players with hip ROM deficits. Hip ROM deficits have also been associated with hip, groin, and knee injuries in soccer, [16][17][18][19] tennis 20 and ice hockey.…”
Section: It Has Been Estimated That Approximately 45 Millionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some research has been performed on the relationship between hip ROM and throwing injuries among young baseball players. 10,26,27 Sakata et al 28 reported that a prevention program consisting of 9 stretching and 9 strengthening exercises could prevent elbow injury and improve several indicators of physical function, such as shoulder ROM and hip IR ROM, as well as thoracic kyphosis. A single cross-sectional study showed a significant association between medial elbow injury and hip IR ROM on the stride side.…”
Section: Discussionmentioning
confidence: 99%
“…If this rotation is inefficient, the medial elbow is likely to be injured due to an increase in mechanical stress on the elbow 9) . Saito et al 10) reported that hip IR ROM in adolescent baseball players with elbow pain was decreased in comparison to that without elbow pain. Among studies of muscle strength, Donatelli et al 11) reported that shoulder ER strength and shoulder ER strength-to-IR strength (ER-to-IR) ratio on the throwing side were lower compared to the nonthrowing side, while strength of shoulder IR and lower *Correspondence: morifujit@kawasakigakuen.ac.jp trapezius (LT) on the throwing side were stronger than those on the non-throwing side of professional baseball players, suggesting that the repeated throwing motion affects strength of rotator cuff and scapular muscles.…”
Section: Introductionmentioning
confidence: 99%